2.5D coupled FEM-SBFEM analysis of ground vibrations induced by train movement. Issue 104 (January 2018) - Yaseri, A.; Bazyar, M.H.; Javady, S.
Abstract: 2.5D models are efficient tools for dynamic analysis of structures that are longitudinally invariant. In this work, a two-and-a-half dimensional (2.5D) coupled finite element method-scaled boundary finite-element method (FEM-SBFEM) is utilized to study the induced ground vibration of passing trains. By applying Fourier transformation in the longitudinal direction, the SBFE equations in the frequency-wave number domain is presented. The unbounded domain is simulated by SBFEM. The coupling with the 2.5D FEM is straightforward. The bounded domain is modelled by FEM and the track with the use of Euler–Bernoulli beam. A number of available analytical solution results are used to verify accuracy of proposed methods in both time and frequency domains. The results were in good agreement with the analytical solution. The effect of speed of the moving load on the ground response is shown. Also 2.5D FEM-SBFEM is used in the analysis of underground train-induced ground vibrations. 2.5D results are in reasonable agreement with 3D results. Highlights: Derivation of scaled boundary finite element equations for a longitudinally invariant medium. Coupling of scaled boundary finite element with finite element methods. Comparison of the new 2.5D method results with the results of a 3D practical example.